Identification of Candida haemulonii Complex Species: Use of ClinProToolsTM to Overcome Limitations of the Bruker BiotyperTM, VITEK MSTM IVD, and VITEK MSTM RUO Databases - Grenfell, Rafaella C.; da Silva Junior, Afonso R.; Del Negro, Gilda M. B.; Munhoz, Regina B.; Gimenes, Viviane M. F.; Assis, Diego M.; Rockstroh, Anna C.; Motta, Adriana L.; Rossi, Flavia; Juliano, Luiz; Benard, Gil; de Almeida Júnior, João N. (Frontiers in Microbiology, 2016)
Candida haemulonii is now considered a complex of two species and one variety: Candida haemulonii sensu stricto, Candida duobushaemulonii and the variety Candida haemulonii var. vulnera. Identification (ID) of these species is relevant for epidemiological purposes and for therapeutic management, but the different phenotypic commercial systems are unable to provide correct species ID for these emergent pathogens. Hence, we evaluated the MALDI-TOF MS performance for the ID of C. haemulonii species, analyzing isolates/strains of C. haemulonii complex species, Candida pseudohaemulonii and Candida auris by two commercial platforms, their databases and softwares. To differentiate C. haemulonii sensu sctricto from the variety vulnera, we used the ClinProTools™ models and a single-peak analysis with the software FlexAnalysis™. The Biotyper™ database gave 100% correct species ID for C. haemulonii sensu stricto, C. pseudohaemulonii and C. auris, with 69% of correct species ID for C. duobushaemulonii. Vitek MS™ IVD database gave 100% correct species ID for C. haemulonii sensu stricto, misidentifying all C. duobushaemulonii and C. pseudohaemulonii as C. haemulonii, being unable to identify C. auris. The Vitek MS™ RUO database needed to be upgraded with in-house SuperSpectra to discriminate C. haemulonii sensu stricto, C. duobushaemulonii, C. pseudohaemulonii and C. auris strains/isolates. The generic algorithm model from ClinProTools™ software showed recognition capability of 100% and cross validation of 98.02% for the discrimination of C. haemulonii sensu stricto from the variety vulnera. Single-peak analysis showed that the peaks 5670 m/z, 6878 m/z or 13750 m/z can distinguish C. haemulonii sensu stricto from the variety vulnera.